Ergotism: Case Report and Review of the Literature - Liegl, Claudia A.; McGrath, Michael A. (International Journal of Angiology, 2016)
A case of ergotism is presented to illustrate the role of duplex ultrasonography in the diagnosis and management of this nonatherosclerotic cause of peripheral arterial disease. Historical aspects of ergotism are discussed together with reference to the relative vulnerability of different segments of the arterial circulation. Our case emphasizes the potential for complete reversibility of the vascular changes if recognized early.
Keywords: ergotism; ergot alkaloids; Claviceps purpurea; nonatherosclerotic arterial disease; lower limb ischemia; migraine; duplex ultrasound